Faith Habitus as a Multidisciplinary Approach in the Critical Analysis of Christian Religious Education - Rocky Agustry Vernando Simamora (Indonesian Journal of Christian Education and Theology, 2026)
In the context of contemporary social change, Christian Religious Education (CRE) faces serious challenges such as faith formalism, exclusivism, and social inequality, problems that are further compounded by a mono-disciplinary and cognitively transmissive approach to teaching faith. These conditions call for a renewed educational paradigm that holistically integrates theological, social, and pedagogical dimensions. This article aims to critically examine the gap between faith teachings and social praxis in CRE, while proposing the concept of faith habitus as a conceptual contribution. The study employs a qualitative–conceptual approach with an interdisciplinary analytical design, drawing on dialogue between Christian education theology (Thomas Groome), the social theory of habitus (Pierre Bourdieu), and experience-based pedagogy (John Dewey). The analysis shows that interdisciplinary integration enables faith to be understood as a spiritual–social disposition shaped through reflective education and social praxis. The concept of faith habitus is positioned as a theoretical and practical framework that bridges the gap between faith teachings and social reality, offering a transformative strategy to address social inequalities within the Church and Christian schools.